Physical activity and quality of life with and without diabetes mellitus - Anke Hanssen-Doose (2009)
Background Physical activity is important in preventing and managing type-2 diabetes. Physical inactivity is globally one of the biggest public health hazards. The aim of this study was to assess the physical activity of individuals with diabetes using a German representative population sample. Methods Subgroups of 248 individuals with diabetes and 3450 controls without diabetes were identified from a larger representative sample, the German National Health and Examination Survey. The subgroup of the cross-sectional study was 40 to 70 years old. The participants completed a questionnaire and underwent a physical examination. Results Most of the individuals with diabetes (between 84% and 92%) did not meet the recommended standard of 30 minutes or more of moderate-intensity physical activity on most, preferably all, days of the week. 67% reported no sports activities in the past three months. Of the controls, 78% - 84% did not attain a sufficient physical activity level, 49% reported no sports in the last three months. Compared to the controls without diabetes, the individuals with diabetes had a significantly lower quality of life (SF-36). After controlling for sociodemographic variables and quality of life, diabetes was associated with physical inactivity.
Keywords: Diabetes; Physical Activity; Exercise; Quality of life